The Evaluation of Hospital Returns in Developing Countries - Diesfeld, H. J. (Methods of Information in Medicine, 1970)
A method is presented to improve the applicability of information derived from hospital returns. This method may also serve as a tool for the evaluation of hospital services and for regional hospital planning.Hospital returns should report in the form of »hospital recording rates« for each of the recorded diseases per year of observation. The »hospital recording rate« is the observed number of each diagnosis in a given period of time, divided by the »effective population« of the »hospital catchment area«. The »hospital catchment area« and the »effective population« are defined by scores reflecting the estimated »degree of centrality«, which is considering the attractivity and accessibility of the single hospital and the demographic situation in the hospital area. The »degree of centrality« can be compared with the regional mean score in order to categorize each hospital within the infrastructure of hospital services in that region. This procedure can supply valuable information for regional hospital planning.